Pendidikan Pra Nikah sebagai Upaya Mencegah Perceraian dan Stunting di KUA Colomadu - Rika Sari; Istanto Istanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
There are cases of divorce and stunting in Colomadu District anticipated to a deficiency of interpretation of prospective couples of prospective couples in building a good household. So this research aims to define the implementation of pre-marital education as an effort to prevent divorce and stunting at KUA Colomadu as well as obstacles in implementing premarital education at KUA Colomadu. This research uses field research with qualitative data through a sociological approach. The research location is KUA Colomadu, Karanganyar Regency, Central Java. The duration of the research took place from November 2024 to December 2024. Data sources for this research include the Head of KUA Colomadu, and officers at KUA Colomadu as well as officers at Community Health Center Colomadu 1. Data collection techniques use field data with several methods, namely interviews, observation and document study. The data analysis technique used is the data analysis technique from Miles & Huberman, namely data presentation, data reduction, and conclusions. The research results show that the implementation of pre-marital education at KUA Colomadu has been going well as evidenced by the decrease in the number of divorce cases every year in Colomadu District, while KUA Colomadu is still trying to overcome stunting in children. Obstacles in implementing premarital education at KUA Colomadu are limited funds for organizing pre-marital education, minimal awareness of prospective brides and grooms to take part in activities, and pocket books provided for prospective brides and grooms are still limited.